A Detailed Review On Medical Image Compression - Verma, Amit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current article is a scientometric analysis of the research articles on the topic “Medical Image Compression”. Scopus and WoS databases have been used for downloading the papers related to the above discussed topic. PRISMA guideline have been used for the selection of the articles. A total 884 articles have been downloaded and 397 have been selected and analyzed with VOS viewer.